The zero night - Freeman, Brian, 1963- (Freeman, Brian, 1963- Jonathan Stride novel., 2023)
"Attorney Gavin Webster says he paid $100,000 in ransom money to the men who kidnapped his wife. Now they've disappeared with the cash, and she's still missing. Gavin claims to be desperate to find her--but Stride discovers that the lawyer had plenty of motive to be the mastermind behind the crime. Even as Stride digs for the truth about Gavin Webster and his wife, he must also deal with a crisis in his own marriage. But all he can do is keep moving forward--because Stride fears the Webster kidnapping may be only one part of a horrific murder conspiracy"--